From Missionary Tradition to Liberal Leadership: Robert College, 1918-1970* - ERKEN, ALİ (My University, 2023)
ABSTRACT: This article analyses the transformation of Robert College, the first American college founded abroad, from 1923 to 1970. Based on a careful investigation of Robert College archives and personal accounts of the College staff, it contends that the school’s missionary character acquired a new identity after the foundation of Republican Turkey. Robert College gradually abandoned its missionary tradition to become an institution of liberal learning in the service of westernizing Turkey. The College presidency and trustees have long elaborated on the new context and trends in liberal education in the United States. At the same time, the Turkish officers and graduates quickly adjusted to this new character immersed in secular values. The College’s transition involved a shared commitment going beyond political partnership, reflecting an intellectual vision that came out of long years of negotiations within the College establishment. Keywords: Missionaries, liberal education, history of United States, history of Turkey
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Missionaries; liberal education; history of United States; history of Turkey